Implementation of the Peer Tutoring Method in Overcoming Students' Learning Difficulties in the Al-Qur'an and Hadith Subject at MI Al-Amien Tegal - Matandi Matandi; Achmad Maulidi (Madrasah Al-Wathoniyah : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
The quality of learning demands the application of interesting models and methods that actively engage students to achieve effective learning objectives. The low learning achievement of students in the Al-Qur'an Hadis subject in Class VI MI Al-Amien Tegal is indicated to be caused by a learning process that has not actively involved the students. This research aims to analyze students' learning conditions and describe the implementation of the Peer Tutoring learning method as a solution to overcome learning difficulties. This study uses a qualitative approach. Data were collected through observation, interviews, and documentation techniques. Data analysis was carried out qualitatively, namely by describing the data found in the field to draw a final conclusion after going through the process of reduction and verification. The implementation of the Peer Tutoring method in addressing students' learning difficulties covers three stages: planning, implementation, and evaluation. The planning stage serves as the initial step for supervising teachers to address student criteria. The evaluation results show that the application of Peer Tutoring succeeded in overcoming the main problem, namely the lack of active student involvement, thereby providing a positive impact in improving students' learning achievement, which was previously unsatisfactory. The Peer Tutoring learning method proved to be the right and effective choice to be applied to the Al-Qur'an Hadis subject in Class VI MI Al-Amien Tegal. This method successfully created a more active learning environment, thus enabling the overcoming of learning difficulties and improving students' achievement results.